Insight into the mechanism of selective mono-N-methylation of aniline on Cu1-xZnxFe2O4: a DRIFTS study - Vijayaraj, M.; Murugan, B.; Shubhangi B. Umbarkar; Hegde, S. G.; Gopinath, Chinnakonda S. (Journal of Molecular Catalysis A - Chemical, 2005)
Mechanism of selective mono-N-methylation of aniline with methanol on Cu1-xZn2FeO4 catalysts was investigated in detail. The interaction of reactants (aniline. methanol and methanol: aniline) and possible products (N-methylaniline (NMA), N,N-dimethylaniline (DMA) and o-toluidine (OT)) on catalysts surface was studied by temperature-dependent in situ FTIR spectroscopy. Methanol adsorbs dissociatively over catalysts surface at 373 K as methoxy species and is oxidized to formate species at high temperature through dioxymethylene and/or formaldehyde as a surface intermediate species. On the other hand, adsorption of aniline:methanol mixtures shows that methanol oxidation was completely hindered in the presence of aniline. Aniline adsorbs on the Lewis acid sites at <= 373 K with phenyl ring oriented in a perpendicular manner to the catalyst surfaced however, N-H bond scission occurs above 373 K. A comparison of adsorbed NMA and methanol: am line (3:1) mixture on Cu0.5Zn0.5Fe2O4 shows NMA forms from the reaction mixture at 473 K. However, maximum activity at 573 K in catalytic reaction studies suggests that desorption limits the methylation kinetics. FTIR study displays stable aniline and methyl species on ZnFe2O4 even at 573 K; however. no methyl species is detected on Cr0.95Zn0.05Fe2O4 at 473 K due to methanol reforming reaction and that limits the overall reaction and hence low catalytic activity. It is proposed that methanol is protonated on catalysts surface by the labile H+ due to N-H bond scission. Co-adsorption of acidity probes with aniline and methanol indicates that aniline methylation takes place at single acid-base site. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Aniline; Cu1-xZnxFe2O4; desorption limited; DRIFT; IR; Methanol; N-methylaniline; N-methylation; reaction mechanism

Transesterification of diethyl oxalate with phenol using MoO3/SiO2 catalyst - Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Applied Catalysis A-General, 2005)
Transesterification of diethyl oxalate (DEO) with phenol to form diphenyl oxalate (DPO) has been carried out in liquid phase using MoO3/ SiO2 solid acid catalyst with high conversion and 100% selectivity. A series Of MoO3/SiO2 catalysts with different Mo loadings (1-20 wt%) were prepared using sol-gel technique and characterized using X-ray diffraction analysis (XRD), BET specific surface area, temperature-programmed desorption (TPD) of ammonia, and FTIR spectroscopic analysis of adsorbed pyridine. XRD analysis revealed the amorphous nature of the catalyst up to 10 wt% MoO3 loading and the formation of crystalline α-MoO3 phase on amorphous silica support with higher MoO3 loading. BET surface area showed high surface area for catalysts prepared by sol-gel technique with lower MoO3 content; the surface area decreases with increasing MoO3 loading. Ammonia TPD shows much higher acid strength compared to the catalysts prepared by impregnation technique. Among the series of catalysts prepared, MoO3/SiO2 containing 1 wt% MoO3 was found to be the most active catalyst for transesterification reaction, with a maximum DEO conversion of 80.9 and 100% selectivity for DPO. The effects of reaction temperature and catalyst concentration on conversion and product selectivity have been investigated. © 2005 Elsevier B.V. All rights reserved.
Keywords: diethyl oxalate; diphenyl oxalate; MoO3/SiO2; sol-gel technique; transesterification

Vapor phase oxidation of 4-fluorotoluene over vanadia-titania catalyst - Maurya, S. K.; Patil, P.; Shubhangi B. Umbarkar; Gurjar, M. K.; Dongare, Mohan K.; Rudiger, S.; Kemnitz, E. (Journal of Molecular Catalysis A - Chemical, 2005)
The vapor phase oxidation of 4-fluorotoluene has been carried out over vanadia-titania catalysts with moderate conversion and selectivity for 4-fluorobenzaldehyde. Two series of V2O5/TiO2 catalysts with 1-10 mol% vanadia were prepared by sol-gel technique using vanadium and titanium peroxide as vanadia and titania precursors respectively and by impregnation technique using vanadium peroxide on anatase titania support. The samples were characterized by X-ray diffraction, NH3-TPD, FT-IR and BET surface area measurements. The XRD of the catalysts prepared by impregnation technique showed retention of the anatase titania whereas the catalysts prepared by sol-gel technique showed the formation of rutile titania with minor amount of anatase phase at lower vanadia content (1-3 %), which completely transformed into anatase phase at higher vanadia loading. The samples prepared by sol-gel method showed higher acidity and surface area compared to the samples prepared by impregnation. Pyridine adsorption study by FT-IR revealed the presence of Lewis acidity at lower vanadia loading (1-3 %) and presence of both Lewis as well as Bronsted acidity at higher vanadia loading. The catalytic activity for oxidation of 4-fluorotoluene increased with vanadia loading in the sol-gel catalysts. The catalysts prepared by impregnation technique were found to be less active. However the selectivity for 4-fluorobenzaldehyde decreased with increase in vanadia content. The influence of vanadia loading, reaction temperature and contact time on the catalytic activity for 4-fluorotoluene oxidation has been investigated. The structure of the catalyst and its catalytic activity has been correlated. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Catalyst; fluorotoluene; Oxidation; vanadia-titania; vapor phase

Regioselective nitration of cumene to 4-nitro cumene using nitric acid over solid acid catalyst - Mathew, Sanyo M.; Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Catalysis Communications, 2006)
The regioselective nitration of cumene to 4-nitro cumene (4-NC) has been carried out using 70% nitric acid over MoO3/SiO2 solid acid catalyst with high conversion (62%) and selectivity (68%) for 4-NC. A series of MoO3/SiO2 catalysts with different MoO3 loadings (1-20 mol%) were prepared by sol-gel technique and characterized using different characterization techniques. XRD analysis revealed the amorphous nature of the catalyst up to 10-mol% MoO3 loading and formation of alpha-MoO3 crystalline phase on amorphous high surface area mesoporous silica support at higher MoO3 loading. Maximum conversion and selectivity has been obtained with slower addition of nitric acid and simultaneous azeotropic removal of water formed during the reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: cumene; nitration; ring nitration; side chain nitration; solid acid catalyst

Synthesis of tinidazole by condensation-oxidation sequence using MoO3/SiO2 bifunctional catalyst - Chandorkar, J. G.; Shubhangi B. Umbarkar; Rode, C. V.; Kotwal, V. B.; Dongare, Mohan K. (Catalysis Communications, 2007)
Antimicrobial drug, tinidazole has been synthesized by condensation of 2-methyl,5-nitro-imidazole and 2-ethyl-thio-ethanol over MoO3/SiO2 catalyst to obtain 1-(2-ethyl-thio-ethanol)-2-methyl-5-nitro-imidazole which is further oxidized using hydrogen peroxide using the same MoO3/SiO2 catalyst to obtain tinidazole. MoO3/SiO2 catalyst (20%), synthesized by sol-gel process showed the highest acid strength and was successfully demonstrated to catalyze both condensation and oxidation in the synthesis of tinidazole. Due to the bifunctional activity of the catalyst, the use of acetic acid for condensation step and tungstic acid or ammonium molybdate for oxidation step in the conventional synthesis of tinidazole could be eliminated, thus making it an environmentally benign process. The catalysts could be recycled five times without any appreciable loss in the conversion and selectivity showing the potential for. the use of MoO3/SiO2 as bifunctional catalyst for the production of this industrially important compound. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: antimicrobial drug; condensation; MoO3/SiO2; Oxidation; solid acid catalyst; tinidazole

Selective cis-dihydroxylation of olefins using recyclable homogeneous molybdenum acetylide catalyst - Biradar, Ankush V.; Sathe, Bhaskar R.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Journal of Molecular Catalysis A-Chemical, 2008)
Selective cis-dihydroxylation of various olefins has been carried out using molybdenum acetylide complex CpMO(CO)(3)(C CPh) (1) as catalyst and hydrogen peroxide as an efficient and environmentally benign oxidant. In case of cyclohexene, very high conversion (95%) and selectivity (86%) for cis-dihydroxylated product has been achieved using H2O2 as an oxidant and t-butanol as a solvent. cis-Dihydroxylation of other substrates like styrene, a-methyl styrene, limonene and cyclopentene has also been carried out with very high selectivity for diol. The catalyst and intermediate species have been characterized using FT-IR, UV-vis spectral analysis and XPS studies as well as cyclic voltametric studies. These studies suggest that molybdenum oxo-peroxo complex is the catalytically active species. The intermediate blue complex when characterized by ESI MS suggested the formation of dimeric molybdenum complex and XPS and cyclic voltametric studies confirm the presence of mixed valence Mo(V) and Mo(VI) in the reaction intermediate. Based on the characterization results possible mechanism for dihydroxylation is proposed. Interestingly, even though the catalyst is homogeneous; it could be recovered quantitatively by extraction in aqueous phase and recycled five times without any appreciable loss in cyclohexene conversion and selectivity for cis-1,2-cyclohexanediol. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: acetylide complex; cis-dihydroxylation; Homogeneous catalysis; Hydrogen peroxide; recyclable

Selective N-oxidation of aromatic amines to nitroso derivatives using a molybdenum acetylide oxo-peroxo complex as catalyst - Biradar, Ankush V.; Kotbagi, Trupti V.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Tetrahedron Letters, 2008)
The molybdenum acetylide oxo-peroxo complex obtained in situ by the treatment of the corresponding molybdenum acetylide carbonyl complex, CpMo(CO)(3)(C CPh); Cp = eta(5-)C(5)H(5) with H(2)O(2), has been used as an efficient catalyst for selective N-oxidation of primary amines to nitroso derivatives. Excellent amine conversion (up to 100%) and very high selectivity for nitroso compounds (99%) have been obtained using 30% hydrogen peroxide as an oxidant. The oxo peroxo, Mo(VI) complex has also been found to be very active for the oxidation of various substituted primary aromatic amines with electron donating as well as electron withdrawing substituents on the aromatic ring. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: aromatic amine; Homogenous catalyst; Hydrogen peroxide; Molybdenum complex; nitroso; Oxidation; Oxo-peroxo

Acetalization of glycerol using mesoporous MoO3/SiO2 solid acid catalyst - Shubhangi B. Umbarkar; Kotbagi, Trupti V.; Biradar, Ankush V.; Pasricha, Renu; Chanale, Jyoti; Dongare, Mohan K.; Mamede, Anne-Sophie; Lancelot, Christine; Payen, Edmond (Journal of Molecular Catalysis A-Chemical, 2009)
Acetalization of glycerol with various aldehydes has been carried out using mesoporous MoO3/SiO2 as a solid acid catalyst. A series of MoO3/SiO2 catalysts with varying MoO3 loadings(1-20 mol%) were prepared by sol-gel technique using ethyl silicate-40 and ammonium heptamolybdate as silica and molybdenum source respectively. The sol-gel derived samples were calcined at 500 degrees C and characterized using various physicochemical characterization techniques. The XRD of the calcined samples showed the formation of amorphous phase up to 10 mol% MoO3 loading and at higher loading of crystalline alpha-MoO3 on amorphous silica support. TEM analyses of the materials showed the uniform distribution of MoO3 nanoparticles on amorphous silica support. Raman spectroscopy showed the formation of silicomolybdic acid at low Mo loading and a mixture of alpha-MoO3 and polymolybdate species at high Mo loadings. Moreover the Raman spectra of intermediate loading samples also suggest the presence of beta-MoO3. Acetalization of glycerol with benzaldehyde was carried out using series of MoO3/SiO2 catalysts with varying MoO3 loadings (1-20 mol%). Among the series, MoO3/SiO2 With 20 mol% MoO3 loadings was found to be the most active catalyst in acetalization under mild conditions. Maximum conversion of benzaldehyde (72%) was obtained in 8 h at 100 degrees C with 60% selectivity for the six-membered acetal using 20% MoO3/SiO2. Interestingly with substituted benzaldehydes under same reaction conditions the conversion of aldehydes decreased with increase in selectivity for six-membered acetals. These results indicate the potential of this catalyst for the acetalization of glycerol for an environmentally benign process. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acetalization; Aldehyde; Glycerol; Silicomolybdic acid; solid acid

Selective oxidation of aromatic primary alcohols to aldehydes using molybdenum acetylide oxo-peroxo complex as catalyst - Biradar, Ankush V.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Tetrahedron Letters, 2009)
Selective oxidation of various aromatic alcohols to aldehydes has been carried out with very high conversion (90%) and selectivity (90%) for aldehydes using cyclopentadienyl molybdenum acetylide complex, CpMo(CO)(3)(C CPh) (1) as catalyst and hydrogen peroxide as environmentally benign oxidant, Water-soluble Mo acetylide oxo-peroxo species is formed in situ after reaction of I with aqueous hydrogen peroxide during the Course of reaction as catalytically active species. Interestingly even though the catalyst is homogeneous it Could be recycled very easily by separating the products in organic phase and catalyst in aqueous phase using separating funnel. Even after five recycles no appreciable loss in alcohol conversion and aldehyde selectivity was observed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Homogenous catalyst; Hydrogen peroxide; Molybdenum complex; Oxidation; Oxo-peroxo; Primary aromatic alcohol

Support modification to improve the sulphur tolerance of Ag/Al2O3 for SCR of NOx with propene under lean-burn conditions - Jagtap, Neelam; Shubhangi B. Umbarkar; Miquel, Pierre; Granger, Pascal; Dongare, Mohan K. (Applied Catalysis B-Environmental, 2009)
Ag/Al2O3 catalysts with 1 wt% SiO2 or TiO2 doping in alumina support have been prepared by wet impregnation method and tested for sulphur tolerance during the selective catalytic reduction (SCR) of NOx using propene under lean conditions, Ag/Al2O3 showed 44% NOx conversion at 623 K, which was drastically reduced to 21% when exposed to 20 ppm SO2. When Al2O3 support in Ag/Al2O3 Was doped with 1 wt% SiO2 or TiO2 the NOx conversion remained constant in presence of SO2 showing the improved sulphur tolerance of these catalysts. Subsequent water addition does not induce significant deactivation. On the contrary, a slight promotional effect on the activity of NO conversion to nitrogen is observed after Si and Ti incorporation. FTIR study showed the sulphation of silver and aluminum sites of Ag/Al2O3 catalysts resulting in the decrease in the formation of reactive intermediate species such as -NCO, which in turn decreases NOx conversion to N-2. In the case of Ag/Al2O3 doped with SiO2 or TiO2, formation of silver sulphate and aluminum sulphate was drastically reduced, which was evident in FTIR resulting in remarkable improvement in the sulphur tolerance of Ag/Al2O3 catalyst. These catalysts before and after the reaction have been characterized with various techniques (XRD, BET surface area, transmittance FTIR and pyridine adsorption) for physico-chemical properties. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ag/Al2O3; Aluminum sulphate; DRIFTS; Selective catalytic reduction; Silver sulphate; SiO2; Sulphur tolerance; TiO2

Synthesis of catalytically active porous platinum nanoparticles by transmetallation reaction and proposition of the mechanism - Pasricha, Renu; Bala, Tanushree; Biradar, Ankush V.; Shubhangi B. Umbarkar; Sastry, Murali (Small, 2009)
A facile method for the synthesis of porous platinum nanoparticles by transmetallation reactions between sacrificial nickel nanoparticles and chloroplatinic acid (H(2)PtCl(6)) in solution, as well as at the constrained environment of the air water interface, using a Langmuir-Blodgett instrumental setup is presented. To carry out the transmetallation at the air-water interface hydrophobized nickel nanoparticles are assembled as a monolayer on the sub phase containing platinum ions. The porous Pt nanoparticles obtained as a result of the reaction are found to act as extremely good catalysts for hydrogenation reaction. The products are well characterized by TEM, HRTEM, EDAX, and STEM. Attempts are made to postulate the plausible mechanism of this reaction to generate this kind of nanoparticle with controllable geometric shape and structure. This simple strategy has the potential to synthesize other nanomaterials of interest too.
Keywords: Catalysts; Interfaces; Nickel nanoparticles; porous platinum; Transmetallation

NO reduction under diesel exhaust conditions over Au/Al2O3 prepared by deposition-precipitation method - Miguel, P.; Granger, P.; Jagtap, Neelam; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dujardin, Christophe (Journal of Molecular Catalysis A-Chemical, 2010)
Gold supported on alumina was prepared by urea deposition-precipitation method and compared to silver supported on alumina for the selective catalytic reduction of NO by hydrocarbons under lean conditions. The catalyst showed activity in the reduction of NO and 100% selectivity towards N-2 in the temperature range 300-350 degrees C. At higher temperature the NO conversion decreased due to competitive oxidative reactions of the reductants. XPS analysis confirmed the good stability of gold nanoparticles deposited on alumina. Infrared studies showed the formation of various adsorbed species (formates, carboxylates, ad-NOx and cyanide) on the catalyst surface. Addition of H-2 to the feed containing decane enhanced the formation of these species on the catalyst surface as well as the catalytic activity for the NO conversion to N-2. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Deposition-precipitation; Gold; In situ IR; NO reduction; XPS

Vanadia-titania thin films for photocatalytic degradation of formaldehyde in sunlight - Akbarzadeh, Rokhsareh; Shubhangi B. Umbarkar; Sonawane, Ravindra S.; Takle, Srikant; Dongare, Mohan K. (Applied Catalysis A-General, 2010)
Thin films of vanadia-titania with good adhesion to the substrates have been deposited on various substrates such as glass slides, glass helix and silica raschig rings by simple sol-gel dip coating process using vanadium and titanium peroxide gel. The optimum concentration of vanadia in titania for obtaining good uniform viscous gel was found to be 0.5-4 wt% beyond which the vanadia particles disturb the gel network, resulting in the formation of a gelatinous precipitate. The films of vanadia-titania as well as the dried powder of the bulk gel were characterized by different characterization techniques. Optical characterization by UV-vis spectrophotometer showed a shift in optical absorption wavelength to the visible region that may be due to the incorporation of vanadia into titania structure. The XRD revealed the formation of anatase phase in pure titania as well as titania with up to 2% vanadia loading, whereas formation of rutile as minor phase along with anatase as major phase was observed at higher vanadia loading. The XRD did not show any peaks of vanadia phase up to 5% vanadia loading indicating either incorporation of vanadia into titania structure or high dispersion of amorphous vanadia on titania support. The pure and vanadia doped TiO(2) thin films were evaluated for their photocatalytic activity for degradation of methylene blue as a model pollutant under sunlight. Doping Of V(2)O(5) in TiO(2) showed an increase in the photo-degradation rate of methylene blue by a factor of 3-6.6 times compared to pure TiO(2). The highest rate has been obtained for 4% V(2)O(5)-doped TiO(2) films. Vanadia doped TiO(2) thin films were also found to be very active for photocatalytic degradation of formaldehyde from aqueous solution in sunlight. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Formaldehyde; Methylene blue; Photocatalysis; Sunlight; Thin films; V(2)O(5)/TiO(2)

One-pot synthesis of 2,4,5-trisubstituted imidazoles using MoO3/SiO2, an efficient and recyclable catalyst - Bhosale, Sidhanath V.; Kalyankar, Mohan B.; Nalage, Santosh V.; Bhosale, Dattatry S.; Pandhare, Swati L.; Kotbagi, Trupti V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Synthetic Communications, 2011)
[image omitted] A simple one-pot synthesis has been developed for the synthesis of 2,4,5-trisubstituted imidazoles using an efficient and recyclable MoO3/SiO2 solid acid catalyst by condensation of benzil or benzoin, benzaldehyde, and ammonium acetate in acetonitrile as a solvent. Using this solid catalyst, the reactions could be carried out under mild reaction conditions with very good yield of imidazoles, up to 95%. This catalyst could be recycled very easily, which makes this methodology environmentally benign.
Keywords: benzil; benzoin; cyclocondensation; imidazoles; MoO3; One-pot; SiO2; solid acid

Deposition-precipitation versus anionic-exchange Au/Al2O3 catalysts: a comparative investigation towards the selective reduction of NOx - Nguyen, D. L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Catalysis Communications, 2012)
Catalytic properties of supported gold catalysts on gamma-Al2O3 prepared by a conventional deposition-precipitation method were compared with those obtained by anionic-exchange for the reduction of NOx by hydrocarbon under lean conditions that simulate Diesel engine exhaust gas. Interestingly, a catalytic activity enhancement is observed after thermal ageing under reactive conditions at 500 degrees C on anionic-exchanged samples which make them suitable for practical developments. On the other hand, the reverse trend is observed on the solids prepared by deposition-precipitation which deactivate at low temperature. Such changes in catalytic properties have been tentatively explained on the basis of textural and structural modifications taking place during thermal ageing under wet atmosphere. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Anionic-exchange; Au catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

One-pot sol-gel preparation for efficient cobalt-molybdenum-titania hydrotreating catalysts - Nguyen, D. L.; Gillot, S.; Souza, D. O.; Blanchard, P.; Lamonier, Carole; Berrier, E.; Kotbagi, T. V.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Cristol, S.; Payen, E.; Lancelot, Christine (Chemcatchem, 2012)
Titania-based hydrodesulfurization catalysts were prepared by using a one-pot solgel method with the titanium peroxo complex as titanium precursor and molybdenum and cobalt precursors dissolved in the aqueous hydrogen peroxide solution used during synthesis. Catalysts with MoO3 loadings varying from 5 to 40 wt?% and a Co/Mo atomic ratio of 0.5 were prepared. Solids with molybdenum loadings below 20 wt?% MoO3 demonstrated poor hydrodesulfurization activity for the model compound thiophene. This was attributed to the presence of a large amount of embedded cobalt and molybdenum species in the titania matrix. A significant increase in the catalytic activity was observed for solids containing 20 and 25 wt?% of MoO3 on which active species appeared to be accessible on the titania surface. Furthermore, the highest conversion obtained on these solgel solids was superior to the highest conversion obtained on reference catalysts prepared through the impregnation of ammonium heptamolybdate and cobalt nitrate on commercial titania.
Keywords: cobalt; heterogeneous catalysis; Molybdenum; sol-gel process; titanium

Selective oxidation of nonrefractory and refractory sulfides by cyclopentadienyl molybdenum acetylide complexes as efficient catalysts - Chandgude, Macchindra G.; Biradar, Ankush V.; Kotbagi, Trupti V.; Puranik, Vedavati G.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Catalysis Letters, 2012)
{The synthesis and catalytic properties of molybdenum acetylide complexes CpMo(CO)(3)(-C CR)
Keywords: Homogeneous catalysis; Molybdenum acetylide; Oxo-peroxo species; Refractory sulfide oxidation

Transesterification of diethyl oxalate with phenol over sol-gel MoO3/TiO2 catalysts - Kotbagi, Trupti; Duy Luan Nguyen; Lancelot, Christine; Lamonier, Carole; Thavornprasert, Kaew-Arpha; Zhu Wenli; Capron, Mickael; Jalowiecki-Duhamel, Louise; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dumeignil, Franck (Chemsuschem, 2012)
The transesterification of diethyl oxalate (DEO) with phenol to form diphenyl oxalate (DPO) has been carried out in the liquid phase over very efficient MoO3/TiO2 solid-acid solgel catalysts. A selectivity of 100?% with a remarkable maximum yield of 88?% were obtained, which opens the route to downstream phosgene-free processes for the synthesis of polycarbonates. Interpretation of the results of various acidity measurements (NH3 and pyridine desorption, methanol oxidation as a probe reaction) allowed us to identify the catalytic sites as Lewis acid sites.
Keywords: heterogeneous catalysis; Lewis acids; Oxidation; sol-gel processes; transesterification

Catalytic dehydration of lactic acid to acrylic acid using calcium hydroxyapatite catalysts - Ghantani, Vidhya C.; Lomate, Samadhan T.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Green Chemistry, 2013)
A series of calcium hydroxyapatite (HAP) catalysts were synthesised with a Ca/P ratio ranging from 1.3 to 1.89 by a co-precipitation method that involved changing the pH of the calcium and phosphorous precursors. The physicochemical characterization by XRD, SEM, BET surface area and CO2 and NH3-TPD techniques confirmed the hydroxyapatite formation. These HAP catalysts were used for the vapour phase dehydration of lactic acid to acrylic acid. The HAP catalyst with a Ca/P ratio of 1.3 was found to be the most efficient catalyst among the synthesised series, which gave 100% conversion of lactic acid and 60% selectivity towards acrylic acid at 375 degrees C when a 50% (w/w) aqueous solution of lactic acid was used. The higher selectivity towards acrylic acid has been correlated to the increased acidity and reduced basicity of the HAP catalyst with a Ca/P ratio of 1.3 compared to the other HAP catalysts. The catalyst was found to be very stable and no deactivation was observed even after 300 h of reaction time. In situ FTIR studies were performed for understanding the mechanistic aspects and showed the formation of calcium lactate as an intermediate species during the dehydration of lactic acid to acrylic acid.

Isolation, characterization, and identification of catalytically active species in the MoO3/SiO2 catalyst during solid acid catalyzed reactions - Kotbagi, Trupti V.; Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K. (Chemcatchem, 2013)
We report the isolation, characterization, and identification of the catalytically active species formed during various acid-catalyzed reactions if silica-supported MoO3 was used as a catalyst. We have reported previously the synthesis and extensive characterization of the silica-supported MoO3 catalyst prepared by the sol-gel process with ammonium heptamolybdate and ethyl silicate-40 as molybdenum and silica precursors, respectively. The TEM images showed uniformly distributed MoO3 nanoparticles on the high-surface area mesoporous silica support and high acidity (0.9mmolg-1) by using temperature-programmed desorption of ammonia (NH3-TPD) analysis. This catalyst has already shown high activity for various acid-catalyzed reactions. To understand the nature of catalytically active species formed during the reaction, the liquid-phase esterification of acetic acid and ethanol was studied as a probe reaction with very high acid conversion (83%) in 8h. During esterification, the reaction mixture turned blue, which indicated a change in the nature of the catalyst under reaction conditions. These catalytically active species formed in the reaction mixture were isolated and extensively characterized by using FTIR, Raman, powder XRD, BET surface area, NH3-TPD, energy dispersive X-ray, and TEM analysis. The characterization results revealed the insitu formation of silicomolybdic acid on the silica surface in the presence of water, which acts as catalytically active species responsible for the acid-catalyzed reactions.
Keywords: esterification reactions; heterogeneous catalysis; Molybdenum; silicon; sol-gel processes

Promising stability of gold-based catalysts prepared by direct anionic exchange for DeNO (x) applications in lean burn conditions - Nguyen, D. -L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Topics in Catalysis, 2013)
Supported gold catalysts on gamma-Al2O3 have been investigated in the catalytic reduction of NO (x) in simulated Diesel exhaust gas conditions. Different parameters have been examined essentially the mode of gold incorporation via classical deposition-precipitation and anionic exchange methods and the nature of the pre-activation thermal treatment. The resistance to thermal ageing under reactive conditions at 500 A degrees C was found completely different with a significant rate enhancement on anionic-exchange samples. Further comparisons also show that the nature of the pre-activation thermal treatment influences the extent of surface reconstructions during thermal ageing with a detrimental effect of reductive pre-treatment on the catalytic performances.
Keywords: Anionic-exchange; Au/Al2O3 catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

Magnesia doped Ag/Al2O3 - sulfur tolerant catalyst for low temperature HC-SCR of NOx - More, Pavan M.; Jagtap, Neelam; Kulal, Atul B.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2014)
A series of magnesia doped Ag/Al2O3 catalysts were prepared by modified impregnation method using boehmite as alumina precursor. The prepared catalysts were characterized and tested for the SCR of NOx using propene as reductant under lean condition. Doping of magnesia improved the low temperature catalytic activity for HC-SCR of NOx as well as sulfur tolerance. Maximum 98% NO conversion with 100% selectivity for N-2 was obtained at 350 degrees C with 7% Mg doping to Ag/Al2O3. The improvement in low temperature activity and the sulfur tolerance has been correlated to decreased acidity after addition of magnesia to alumina support. In situ FTIR study showed that the deactivation in the presence of SO2 was due to the sulfation of silver and aluminum sites in Ag/Al2O3 catalyst, however its formation was suppressed in case of magnesia doped Ag/Al2O3 improving its sulfur tolerance. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: HC-SCR; Low temperature activity; NOx; Sulfur tolerance

Molybdenum(VI) dioxo complexes for the epoxidation of allylic alcohols and olefins - Pandhare, Swati L.; Jadhao, Rajesh R.; Puranik, Vedavati G.; Joshi, Pranaya V.; Capet, Frederic; Dongare, Mohan K.; Shubhangi B. Umbarkar; Michon, Christophe; Agbossou-Niedercorn, Francine (Journal of Organometallic Chemistry, 2014)
Several molybdenum(VI) dioxo complexes have been investigated as catalyst precursors for allylic alcohol epoxidation using mainly hydrogen peroxide as oxidant. All catalysts proved to be efficient and selective for the epoxidation of allylic alcohols provided the olefins were rather electron rich. Indeed, electron poor substrates could be converted selectively into the corresponding unsaturated aldehydes. A chiral dioxomolybdenum complex based on an optically pure tridentate Schiff base ligand was synthesized and characterized. Though that complex provided an efficient epoxidation catalyst for allylic alcohols and olefins, no chiral induction was observed. During the X-ray diffraction analysis, the cooling at 100 K led to the appearance of super-lattice reflections on diffraction patterns reflecting an ordering of the structure. Instead of one organometallic species observed at 298 K, three similar complexes of the same molecular structure could be observed in the asymmetric unit at 100 K. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Allylic alcohol; epoxidation; Molybdenum; Oxidation; Peroxide

Nonstoichiometric calcium pyrophosphate: a highly efficient and selective catalyst for dehydration of lactic acid to acrylic acid - Ghantani, Vidhya C.; Dongare, Mohan K.; Shubhangi B. Umbarkar (RSC Advances, 2014)
Calcium phosphate catalysts were prepared by co-precipitation method using calcium nitrate and mixtures of ammonium and different sodium phosphates as calcium and phosphate precursors, respectively. Depending on the phosphate precursor, the pH of the synthesis mixture changed during the catalyst precipitation. The catalyst characterisation by XRD and ICP revealed the formation of a calcium pyrophosphate structure with varying Ca/P ratio from 1.02 to 0.76 which could be correlated to the different pH of the synthesis solutions. Vapour phase dehydration of lactic acid to acrylic acid was carried out using these calcium pyrophosphate catalysts. Non-stoichiometric calcium pyrophosphate catalyst with Ca/P ratio 0.76 was found to be the most efficient catalyst among the synthesized series with 100% lactic acid conversion and 78% acrylic acid selectivity at 375 degrees C. The higher selectivity for acrylic acid has been correlated to the increased acidity and reduced basicity of non-stoichiometric calcium pyrophosphate compared to other stoichiometric pyrophosphates. In situ FTIR studies showed the formation of a higher amount of calcium lactate on non-stoichiometric compared to stoichiometric pyrophosphate leading to higher selectivity for acrylic acid.

One-pot synthesis of ultrasmall MoO3 nanoparticles supported on SiO2, TiO2, and ZrO2 nanospheres: an efficient epoxidation catalyst - Chandra, Prakash; Doke, Dhananjay S.; Shubhangi B. Umbarkar; Biradar, Ankush V. (Journal of Materials Chemistry A, 2014)
Ultrasmall molybdenum oxide (MoO3) nanoparticles supported on various (SiO2, TiO2 or ZrO2) nanospheres were synthesized in one pot using a reverse micelle method. The prepared catalysts were thoroughly characterized by various physico-chemical methods. TEM images showed uniform dispersion of MoO3 nanoparticles (1.5-4 nm) onto silica (similar to 275 nm). No separate MoO3 particles were identified from TEM for MoO3/TiO2 (similar to 10.5 nm) and MoO3/ZrO2 (similar to 6.5 nm) because AHM reacted with titanium and zirconium hydroxides to form solid solution. Among the prepared catalysts MoO3/SiO2 showed excellent catalytic activity (up to 90% conversion and 100% epoxide selectivity) for olefin epoxidation. The catalyst was successfully recycled up to five cycles without losing much activity and selectivity.

Activation by pretreatment of Ag-Au/Al2O3 bimetallic catalyst to improve low temperature HC-SCR of NOx for lean burn engine exhaust - More, Pavan M.; Nguyen, Duy L.; Granger, Pascal; Dujardin, Christophe; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2015)
Bimetallic Ag-Au/Al2O3 catalyst was synthesised by successive impregnation of 1% Au and 1% Ag on in-house prepared high surface area alumina (450 m(2)/g). The corresponding monometallic catalysts were also prepared by loading 1% Ag or 1% Au on the same high surface area alumina for comparison. The catalysts were characterised by various physico-chemical techniques and tested for SCR activity under lean burn engine exhaust conditions. Ag-Au/Al2O3 catalyst prepared by successive impregnation method showed considerably higher NO reduction (100%) to N-2 compared to 1% Au/Al2O3 (70%) whereas the activity was comparable with that of 1% Ag/Al2O3 (96%). The effect of various pretreatments on SCR activity of Ag-Au/Al2O3 was studied and pretreatment at 250 degrees C in flow of hydrogen was found to give the best results with 100% NO conversion to N-2 at 353 degrees C. Further ageing of the catalyst under reaction feed at 500 degrees C resulted in considerable increase in low temperature activity of bimetallic catalyst with similar to 40% NO conversion at 222 degrees C. Even though the SCR activity of pretreated Ag-Au/Al2O3 and Ag/Al2O3 were comparable, after ageing the Ag-Au/Al2O3 showed significantly higher NO conversion (95%) compared to Ag/Al2O3 (83%) and Au/Al2O3 (70%). The formation of H-2 and CO due to steam reforming of higher hydrocarbon (decane) was evidenced at the temperature of highest deNO(x) activity. Detailed investigation of the textural properties of the pretreated and aged catalysts showed presence of well dispersed metallic Au and Ag-n(delta+) clusters after pretreatment in hydrogen at 250 degrees C. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ag-Au bimetallic catalyst; Catalyst ageing; dispersion; Low temperature HC-SCR; Steam reforming

Highly loaded well dispersed stable Ni species in NiXMg2AlOY nanocomposites: application to hydrogen production from bioethanol - Fang, Wenhao; Paul, Sebastien; Capron, Mickael; Biradar, Ankush V.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Dumeignil, Franck; Jalowiecki-Duhamel, Louise (Applied Catalysis B-Environmental, 2015)
Inexpensive NiXMg2AlOY nanocomposites with high Ni content (Ni wt% > 40%) are developed as efficient catalysts for the sustainable hydrogen production from a mixture of ethanol and water at low temperature. The NiXMg2AlOY nanocomposites are composed of small and uniform nanoparticles (4-6 nm) of NiO, Ni-Mg-(Al)-O and/or MgO. The strong interactions existing between Ni2+ cations and Mg2+ and/or Al3+ cations either in the Ni-Mg-(Al)-O solid solution and/or at the interface of nanoparticles of NiO and/or Ni-Mg-(Al)-O make the catalyst highly active and stable. The behavior of the solids is analyzed in the presence of low and high concentrations of ethanol while maintaining a H2O/EtOH molar ratio of 3. The NiXMg2AlOY catalysts are shown to be efficient toward H-2 production between 250 and 650 degrees C. In the presence of low concentration of ethanol, on the highly loaded Ni compound (Ni12Mg2AlOY), total conversion of ethanol is obtained at 250 degrees C without formation of CO and carbon, and at 300 degrees C a H-2 yield of 3 mol moletEtOH(-1) is obtained without the formation of CO, exhibiting a remarkable stability with the time on stream even if some carbon is formed. In high concentration of ethanol, total conversion of ethanol is obtained at 450 degrees C on the highly loaded Ni compound (Ni12Mg2AlOY). In such conditions, a stable co-generation of carbon nanofibrous materials which amount increases with Ni content is also obtained. The catalytic stability is related to the type and morphology of the carbon species formed. The correlations among the catalyst properties, the catalytic performances and the characterizations are thoroughly discussed. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Hydrogen; Nanofibrous carbon; nickel oxide; Steam reforming

Rational preparation of Ag and Au bimetallic catalysts for the hydrocarbon-SCR of NOx: sequential deposition vs. coprecipitation method - More, Pavan M.; Nguyen, D. L.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Nuns, N.; Girardon, J. S.; Dujardin, Christophe; Lancelot, Christine; Mamede, Anne-Sophie; Granger, P. (Applied Catalysis B-Environmental, 2015)
This study emphasizes the importance of the preparation method for bimetallic Au-Ag catalysts supported on alumina in the selective reduction of NOx by hydrocarbons with gas feed compositions representative of diesel fuelled engine exhaust gas. An optimal balance between oxidative and reductive surface properties is obtained when Au and Ag are successively introduced. Significant re-dispersion processes take place when the catalyst runs at 500 degrees C leading to a gain in activity at low temperature and ascribed to a better interaction between Au and Ag species. Co-precipitation leads to a preferential formation of intermetallic Au-Ag particles which is detrimental to the catalytic performances. Aging at 500 degrees C leads to a significant particle sintering and a strengthening of the metallic character. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Au-Ag particles; Co-precipitation; DeNO(x) reaction; HC-SCR

Silica microspheres containing high density surface hydroxyl groups as efficient epoxidation catalysts - Chandra, Prakash; Doke, Dhananjay S.; Shubhangi B. Umbarkar; Vanka, Kumar; Biradar, Ankush V. (RSC Advances, 2015)
Uniformly sized silica microspheres were synthesized by a hydrolysis-condensation method. The obtained material was etched with a mild aqueous potassium hydroxide solution for different periods of time to break their Si-O-Si bonds and increases the density of hydroxyl groups on their surfaces. The resulting materials were then used as transition metal-free catalysts for oxidation of olefins in the presence of hydrogen peroxide as a green oxidant. The materials were thoroughly characterized using various physicochemical techniques. These highly populated hydroxyl groups on the surface of silica microspheres were proven to be responsible for excellent conversion (up to 93%) and epoxide selectivity (up to 100%) for various olefins. Quantum mechanical calculations also corroborate the experimental findings. Furthermore, both experimental and theoretical studies show that tertiary silanols were present at the active sites of the catalyst surface and were responsible for olefin epoxidation.

Sol-gel synthesised WO3 nanoparticles supported on mesoporous silica for liquid phase nitration of aromatics - Kulal, A. B.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Applied Catalysis B-Environmental, 2016)
A series of WO3/SiO2 catalysts have been prepared by sol-gel method using ammonium metatungstate and ethyl silicate-40 (ES-40) as WO3 and SiO2 precursors respectively. The sol-gel method has led to the formation of WO3 nano-particles of 2-5 nm well dispersed on mesoporous silica along with some WO3' agglomerates. Formation of monoclinic WO3 was seen on the catalysts above 5 wt% WO3 loading by XRD analysis. Silica has shown very high surface area of 606 m(2)/g which decreased gradually upto 368 m(2)/g with 20 wt% WO3 loading. 20 wt% WO3/SiO2 catalyst has shown maximum acidity (0.56 mmol NH3/g) with presence of both Lewis and Bronsted acidity. UV-vis DRS analysis showed formation of polytungstate species along with WO3 on silica surface. The prepared catalysts were used for liquid phase nitration of aromatics using 70% nitric acid as nitrating agent without using any sulfuric acid. Very high conversion (99%) was obtained for p-cresol nitration with very high selectivity (99%) for 2-nitro p-cresol. The water formed during the reaction was removed azeotropically using ethylene dichloride as solvent. In case of o-xylene 74% conversion was obtained with 54% selectivity for 4-nitro o-xylene. The effect of different WO3 precursors on nitration efficiency was studied using sodium tungstate and tungstic acid as precursors. However,ammonium metatungstate showed the highest acidity. Sodium tungstate showed formation of dimer of sodium tungstate which did not show any acidity and hence no activity for nitration. The mechanism for nitration using WO3/SiO2 has been proposed based on polarisation of water on tungsten centre generating Bronsted acidity which can further generate nitronium ion giving subsequently nitration of the aromatic ring. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aromatic nitration; heterogeneous catalysis; Regioselective; Sol-gel synthesis; Water polarization